Education Formulation, Land Tax Calculation, and Completeness of Land Registration Documents - Sinaga, Roulinta Yesvery; Dyastuti, Risqi Mumpuni; Kuahaty, Sarah Selfina; Sihite, Sri Rumada (AIWADTHU: Jurnal Pengabdian Hukum, 2026)
Introduction: Activity devoted to the public. This aim is to provide comprehensive education on the formulation, calculation, tax, land, and equipment file registration in Amahai Village, Central Maluku. Purposes of The Devotion: To increase the understanding of the public to aspects crucial in the registration process, including calculation of Land and Building Acquisition Tax and Final Income Tax, as well as ensure Completeness of required documents. Method of The Devotion: Activities Devotion. This is done through socialization, discussion, interaction, and the provision of easy-to-understand materials. Results Main Findings of the Devotion: Results of activity. This shows significant improvement in participants' knowledge of formulation calculation taxes, especially Land and Building Acquisition Tax and final final Income Tax, as well as a greater understanding of the condition file registration for land. Participants also pointed out that improving awareness will be important to obtain an ownership certificate as proof of legitimate rights. The conclusion of the activity. This is effective education that increases the public's ability to navigate the registration process, reduces potential errors in tax calculations, and minimizes risks associated with incomplete documents.